2014
DOI: 10.1016/j.virusres.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective on the all-in-one retroviral nucleocapsid protein

Abstract: This review aims at briefly presenting a retrospect on the retroviral nucleocapsid protein (NC), from an unspecific nucleic acid binding protein (NABP) to an all-in-one viral protein with multiple key functions in the early and late phases of the retrovirus replication cycle, notably reverse transcription of the genomic RNA and viral DNA integration into the host genome, and selection of the genomic RNA together with the initial steps of virus morphogenesis. In this context we will discuss the notion that NC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 287 publications
0
32
0
Order By: Relevance
“…Indeed, NC is able to cover all HIV-1 RNA in the virion and this may occur in the cell when NC is included in Gag or GagPol or when it is partially cleaved by the protease. 71 These results also explain why, despite containing potent RSSs such as TAR and RRE described in this study, HIV-1 has not been observed to suppress RNAi. 16 Furthermore, when integrated, a self-inactivating lentivirus with no LTR will not express TAR or RRE, therefore confirming the use of RNAi as a valid therapeutic option to target HIV-1 in gene therapy.…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, NC is able to cover all HIV-1 RNA in the virion and this may occur in the cell when NC is included in Gag or GagPol or when it is partially cleaved by the protease. 71 These results also explain why, despite containing potent RSSs such as TAR and RRE described in this study, HIV-1 has not been observed to suppress RNAi. 16 Furthermore, when integrated, a self-inactivating lentivirus with no LTR will not express TAR or RRE, therefore confirming the use of RNAi as a valid therapeutic option to target HIV-1 in gene therapy.…”
Section: Discussionmentioning
confidence: 51%
“…NC is involved in many steps of viral replication including virion assembly, genomic RNA packaging, reverse transcription and integration (Darlix et al, 2014). The CA protein constitutes the major structural protein of the virion core and plays a role in early events such as nuclear entry and DNA integration.…”
Section: Resultsmentioning
confidence: 99%
“…NC exists as a domain of the Gag precursor protein and the partially matured products NCp15 and NCp9, which are generated by the retroviral protease (Mirambeau et al 2010). NC is involved in many steps in the HIV-1 replication cycle, including reverse transcription, selective genome packaging, genome dimerization, genome protection, and integration (Levin et al 2005Darlix et al 2007Darlix et al , 2011Darlix et al , 2014Sleiman et al 2012). During reverse transcription, the nucleic acid chaperone activity of NC facilitates the rearrangement of nucleic acids into their most thermodynamically stable structures.…”
Section: Introductionmentioning
confidence: 99%